2010
DOI: 10.3109/17435390903470101
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary response after exposure to inhaled nickel hydroxide nanoparticles: Short and long-term studies in mice

Abstract: Short and long-term pulmonary response to inhaled nickel hydroxide nanoparticles (nano-Ni(OH)2, CMD = 40 nm) in C57BL/6 mice was assessed using a whole body exposure system. For short-term studies mice were exposed for 4 h to nominal concentrations of 100, 500, and 1000 mg/m3. For long-term studies mice were exposed for 5 h/d, 5 d/w, for up to 5 months (m) to a nominal concentration of 100 mg/m3. Particle morphology, size distribution, chemical composition, solubility, and intrinsic oxidative capacity were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
85
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(91 citation statements)
references
References 46 publications
5
85
0
1
Order By: Relevance
“…20 Other studies involving Ni oxide nanoparticles have also reported the presence of lymphocytic infiltrates in the lung. 21 In the high dose group, foamy macrophages were observed in the alveolar spaces, which are found in various lung diseases. A study by Yuasa and Kanazawa 22 found that foamy macrophages can be derived from monocytes in the blood.…”
Section: Dpv Injection Of Ni Nanoparticles Led To Inflammatory Infiltmentioning
confidence: 99%
“…20 Other studies involving Ni oxide nanoparticles have also reported the presence of lymphocytic infiltrates in the lung. 21 In the high dose group, foamy macrophages were observed in the alveolar spaces, which are found in various lung diseases. A study by Yuasa and Kanazawa 22 found that foamy macrophages can be derived from monocytes in the blood.…”
Section: Dpv Injection Of Ni Nanoparticles Led To Inflammatory Infiltmentioning
confidence: 99%
“…These observed changes may be related to the time course of different parameters and the dynamic nature of the cytokine network after NP exposure. 10 However, some studies have shown that NiONP exposure induces only mild and reversible inflammation. 33,34 Zhang et al 35 found that NiO (20 µg suspended in 50 µL of PBS) exposure induced less neutrophil cell counts, monocyte chemotactic protein-1, and IL-6 levels in BALF compared with the same amount of CuO and Cr 2 O 3 exposure in C57 BL/6 mice.…”
mentioning
confidence: 99%
“…28 Inhalation is the major exposure route of Ni 2+ NPs; AMs and airway epithelial cells are the most important target cells. 10,29 Agglomerates of NiONPs have been shown to induce persistent inflammatory effects and the increased expression of cytokines, such as IL-1β and monocyte chemotactic protein-1. 30 In this study, intratracheal instillation of NiONPs resulted in persistent pulmonary inflammation, which was accompanied by neutrophil, eosinophil, and macrophage infiltration and cytokine secretion.…”
mentioning
confidence: 99%
“…Compared with their bulk counterparts, nanomaterials are often more toxic (Grassian et al, 2006;Pan et al, 2007). For example, a number of toxicological studies using rats have shown that exposure to nanodots induces greater inflammatory and cytotoxic effects than larger-sized particles at equivalent mass concentrations (Grassian et al, 2006;Gillespie et al, 2010;Rossi et al, 2010). Most nanomaterial toxicity studies have focused on nanodots (i.e., particles of various shapes with no predominant dimension, or 0D), and only a few studies have addressed the toxicity of elongated rod-like (1D) nanoparticles (Magrez et al, 2009;Song et al, 2010) or compared 1D nanomaterials with their 0D counterparts (Chithrani et al,2006;Pal et al, 2007;Ispas et al, 2009;Simon-Deckers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%